Construindo valores humanos pelo trabalho coletivo: estudo das práticas de mutirão na ilha do Campompema, Abaetetuba, Pará, Amazônia brasileira - AZEVEDO, Rosicleice do Socorro Ribeiro (2021)
The present article analyzed the practices of multitudes involved in reciprocity in Rio Campompema (Abaetetuba-Pará), locating the different forms of work and relationship between the groups, in an attempt to understand the interpersonal relationships of mutual help among members of the joint efforts, participation of the family, the importance of the mutirão, as this practice occurs in different groups. This is a case study with a qualitative approach. In order to do so, we interviewed 06 residents of the community in question, all of them active in the groupings of the Rio Campompema. As main results, it can be highlighted that the mutirões are social practices that provide possibilities to strengthen relationships of friendship, companionship and help among its members . Another factor that we observed was that most of the Campompema River task forces, such as the farm mutirão; Matapi's fellowship; fish stocks; grocery store management; women's groups; have as main objectives the circulation, through the sale, of products, generating income for the members, which is divided equally. Already the mutirão of the catholic church is different, therefore, the main objective is to help the people in need with small repairs or constructions of houses, bridges, among others. We emphasize the importance of study and others as ways of recognizing that other ways of building exchanges are possible, not just selfish interests.